Competition Law Enforcement in the BRICS and in Developing Countries Legal and Economic Aspects - Jenny, Frederic; Katsoulacos, Yannis; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This contributed volume focuses on competition policy enforcement in BRICS and developing counties. It examines the role and application of economic analysis and evidence in law enforcement procedures, as well as their influence on competition authorities' policy-making. The contributors also address topics such as recent developments in competition law and practice, institutional design, indicators of performance in enforcement, the incorporation of public interest concerns in Competition Authority objectives, procedural fairness, procurement procedures and compulsory licensing.
Introduction.-1 The Institutional Design of Competition Authorities: Debates and Trends -- 2 New Indicators of Competition Law and Policy in 2013 for OECD and Non-OECD Countries -- 3 Cartel Damages to the Economy: An Assessment for Developing Countries -- 4 Public Enforcement of Antitrust Law in China: Perspective of Procedural Fairness -- 5 Antitrust and Compulsory Licensing in BRICS and Developing Countries -- 6 Procurement Procedures and Bid-Rigging in Brazil -- 7 The Nature and use of Economic Evidence in Competition Enforcement -- 8 Economic Analysis in Antitrust: the Case of Brazil -- 9 Economic Evidence in Competition Law Enforcement in India -- 10 Models of Monopoly in the Quarter-Century Development of Russian Competition Policy: Understanding Competition Analysis in the Abuse of Dominance Investigations -- 11 Economic Analysis in Competition Law Enforcement in Russia: Empirical Evidence Based on Data of Judicial Reviews -- 12 The Incorporation of the Public Interest in the Assessment of Prohibited Conduct: A Juggling Act? -- 13 Estimating the Benefits of Anti-Cartel Interventions: The Case of the South African Cement Cartel -- 14 A History of Collusion: The Persistence of Cartels in South Africa -- 15 Application of Hypothetical Monopoly Test (SSNIP) to the Brazilian Market of Ready-Made Meals and the Role of the Department of Economic Studies.
Keywords: Law and economics; Economic policy; Industrial organization; Development economics; International Economic Law, Trade Law